Plastics Materials and Processes : A Concise Encyclopedia - Harper, Charles A.; Petrie, Edward M. (Hoboken, N.J. : Wiley-Interscience, 2003)
"The broad range of professionals involved in plastics and related industries requires a comprehensive, accessible resource on these ubiquitous materials that foregoes cumbersome, technical jargon. Plastics Materials and Processes: A Concise Encyclopedia defines materials, processes, properties, test methods, and other useful information in a straightforward and efficient manner." "Intended for general managers, executives, purchasing and manufacturing personnel, supervisors, engineers, and students, this comprehensive guide will be useful to anyone involved in product design, development, application, manufacturing, marketing, or other periphery functions in the plastics industry. Plastics Materials and Processes provides a concise reference to an extraordinary volume of pertinent material."--BOOK JACKET.
Includes index.
HB
Keywords: Plastics -- Encyclopedias